ZAKAT MANAGEMENT AND ITS ROLE IN POVERTY ALLEVIATION: A LEGAL ANALYSIS OF THE QUR'AN AND LAW NO. 23/2011 - Nassarudin, Ende Hasbi; Azazy, Yusup (VARIA HUKUM, 2024)
His study aims to analyse the effectiveness of zakat management in West Java from the Qur’an and Law Number 23 of 2011 perspectives and its contribution to poverty alleviation. The research adopts a quantitative approach with a descriptive design involving direct observation, interviews with zakat administrators at the provincial and district/city levels of BAZNAS, and a literature review. Primary data were obtained from interviews and field observations, while secondary data include Islamic legal literature, tafsir books, and official documents from BAZNAS. The findings indicate that zakat management in West Java has been systematically structured through BAZNAS and supported by digital technology that enhances transparency and public participation. However, limited zakat literacy and insufficient inter-agency synergy still hinder optimisation. From the Qur’anic perspective, zakat is viewed as a tool for social equity, while Law Number 23 of 2011 provides a legal framework for professional and accountable management. This study concludes that zakat management has significant potential for poverty alleviation through consumptive and productive approaches. However, enhanced collaboration, public literacy, and technological innovation are required to achieve optimal outcomes.